THE STAMP TEST DELIVERS THE MESSAGE ON ERECTILE DYSFUNCTION FOLLOWING HIGH DOSE IMRT FOR PROSTATE CANCER - Keller, Lanea M. M. (2012)
OBJECTIVES: To evaluate erectile function following high dose radiotherapy for prostate cancer using the international index of erectile function (IIEF), expanded prostate cancer index composite (EPIC), and stamp test. METHODS: Men with favorable and intermediate risk prostate cancer were assigned to receive prostate intensity modulated radiotherapy (IMRT) vs. an erectile tissue-sparing IMRT technique on a phase III randomized prospective study. The stamp test, IIEF, and EPIC questionnaires were completed at baseline, 6 months, one year, and two years after IMRT. Sexual Health Inventory for Men (SHIM) scores were abstracted from IIEF questionnaires. A partner questionnaire, designated IIEF-P, modeled after the IIEF but from the perspective of the partner, was collected. RESULTS: Ninety four men enrolled on the trial who completed at least one questionnaire or one stamp test were analyzed. The median age of the patient population was 62.5 years. The median RT dose was 76 Gy (range: 74–80 Gy). At 6-months and one year after high-dose IMRT, a positive stamp result significantly correlated with median EPIC sexual summary, sexual function (EF), and bother subscale scores. Additionally, 6-months after IMRT the stamp test correlated with median IIEF, IIEF EF domain, and SHIM scores. Robust concordance for the IIEF and SHIM results was appreciated between responding patients: partner pairs. CONCLUSIONS: Nocturnal tumescence indicated by a positive stamp test correlates well with established quality of life questionnaires after IMRT. The stamp test should strongly be considered as an objective measure of erectile function in future studies of ED in prostate cancer patients.